Józef Tadeusz Milik and the Publication of the Qumran Fragments of the Aramaic Testament of Levi - Drawnel, Henryk (Revue de Qumran, 2021)
The goal of this study is to discuss and critically evaluate the history of the identification and publication of the Aramaic Testament of Levi, a Jewish priestly composition from the Second Temple period. The role of Józef Tadeusz Milik in the identification, position on the plates, and publication of the Qumran manuscripts of this priestly and scribal text from cave 4, together with his opinions on the manuscript division, has been acknowledged. After the evaluation of the publication of the Aramaic fragments of this priestly composition (4Q213-4Q214b) by M. E. Stone and J.C. Greenfield in DJD XXII, the article discusses, in some detail, Milik’s opinions about the date, composition and division of the Aramaic manuscripts expressed in his unpublished monograph on the Aramaic Testament of Levi. The study leads to the conclusion that Milik’s monograph containing important insights must be published so that a new edition of the Levi composition that will remedy the shortcomings of the earlier treatment of all the manuscripts may be prepared.